Effect of feeding calcium salts of soybean oil fatty acids on physical and chemical characteristics of milk in cows - NADEEM, MUHAMMAD; HUSSAIN, IMTIAZ; ABDULLAH, MUHAMMAD (The Indian Journal of Animal Sciences, 2013)
The present study was conducted to determine the effect of feeding calcium salts of soybean oil on composition of milk fat and characterize the modified milk fat. Sahiwal cows (18) of first and early lactation were stratified into 3 groups in a completely randomized design. Calcium salts of soybean oil fatty acids (CSSFA) were fed at 2 different levels i.e. 150 and 300 g CSSFA/cow/day with third group kept as control. Feeding CSSFA significantly decreased the content of short chain fatty acids and increased the concentration of unsaturated fatty acids in both the treated groups. The milk yield and fat increased with no effect on cholesterol content. Melting point and oxidative stability was also less in the treated groups. Sensory evaluation indicated no effect on color, taste and smell of milk with CSSFA feeding.